(untitled) (Research, Society and Development, 2020)
This study evaluated the potential of four formulations of the entomopathogenic fungus Beauveria bassiana for the control of Thaumastocoris peregrinus. For this, the leaves of Eucalyptus dunni were immersed in each delivery of B. bassiana, isolated IBCB 66, and also in sterile distilled water containing Tween 80® (0.01%) (control), totaling five treatments, with five repetitions each. These leaves were placed in germination boxes containing 10 insects in each and, subsequently, kept in an air-conditioned room (27 ± 2 ° C, 60 ± 10% RH, and 12-h photophase). Record longevity for seven days. The experiment was carried out with adults and also with 3rd instar nymphs of T. peregrinus. These formulations were tested for resistance induction, using organic soybean seeds (standard) sown in sand. Ten days after emergence, 40 µL of treatment suspension was competent in 2 mm cuts made on the top of the cotyledon. Phytoalexins and phenylalanine ammonia lyase (PAL) were determined. All formulations caused a reduction in the longevity of T. peregrinus when compared to the control, standing out as formulations T1 and T2, both for adults and for 3rd instar nymphs of T. peregrinus. The T2 expansion also promotes an increase in the production of phytoalexins and PAL. Thus, the IBCB 66 isolate from B. bassiana, supplied T1, has the potential to control nymphs and adults of T. peregrinus and is also a potential resistance inducer.